2005
DOI: 10.1038/sj.onc.1209233
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of LOH at MMR loci in hereditary non-polyposis colorectal cancer?

Abstract: hMLH1 and hMSH2 can be considered tumor suppressor genes, as both alleles must be inactivated in order to lose the mismatch repair (MMR) function. In this regard, it has been proposed that LOH at MMR loci is a common Knudson's second-hit mechanism in HNPCC patients. However, experimental evidence supporting this view is scarcely found in the literature. We have performed a comprehensive analysis of LOH in 45 HNPCC tumors carrying a germline alteration in MMR loci. Overall, we have detected LOH at MMR loci in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
3
25
0
4
Order By: Relevance
“…Our overall frequency for LOH at MLH1 (31/57, 54.4%) is compatible with frequencies reported for other series, mainly consisting of HNPCC-related CRCs (33-56%) (Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002;Sanchez de Abajo et al, 2006). Our results show that the wt allele is the preferential target for LOH in both CRC and EC (P ¼ 0.006, Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our overall frequency for LOH at MLH1 (31/57, 54.4%) is compatible with frequencies reported for other series, mainly consisting of HNPCC-related CRCs (33-56%) (Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002;Sanchez de Abajo et al, 2006). Our results show that the wt allele is the preferential target for LOH in both CRC and EC (P ¼ 0.006, Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…On the cellular level, MMR gene mutations are not always recessive, but may have dominant-negative effects (Jager et al, 1997;Nicolaides et al, 1998), or be associated with haploinsufficiency (Cejka et al, 2003;Takagi et al, 2003). Furthermore, although initial studies suggested that all LOH events occurring in HNPCC tumors from MLH1 mutation carriers (6/6, 100%) affect the wt allele (Hemminki et al, 1994), a recent investigation found that up to 40% (8/20) of LOH present in HNPCC CRC may target the mutant allele (Sanchez de Abajo et al, 2006). The authors postulated a 'dual' role for LOH: although LOH may contribute to the inactivation of the wt allele ('second hit LOH'), it may also occur as part of tumor progression and affect the mutant allele in tumors in which the wt allele has already been inactivated by other means (Sanchez de Abajo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It was of particular interest to compare our results to the recent work proposing the dual LOH hypothesis for HNPCC (Sanchez de Abajo et al, 2006). The authors reported LOH in 57% (20/35) of HNPCC tumors with MMR germline mutation and showed that in 40% (8/20) of these LOH targeted the mutant allele.…”
supporting
confidence: 55%
“…However, the number of tumors that have actually been studied has not been extensive. In this respect, a recent study reported LOH analyses in 35 Spanish HNPCC tumors carrying a germline mutation in MLH1 or MSH2 (Sanchez de Abajo et al, 2006). LOH was detected in 57% (20/35) of the tumors with a germline mutation but interestingly in 40% (8/20) of these, mutant allele was lost.…”
mentioning
confidence: 99%
“…LOH is common to all human solid tumors and allows expressivity of recessive loss of function mutations of tumor suppressor genes. Therefore, detection of recurrent LOH in a chromosome region is now considered critical evidence of localization of tumor suppressor genes [3,[25][26][27][28] . In the previous study, initial LOH scanning was carried out in 83 sporadic colorectal carcinoma samples with 21 highly polymorphic markers on chromosome 1.…”
Section: Discussionmentioning
confidence: 99%